Anti-collision and anti-impact polyurethane material and preparation method thereof

By adjusting the soft and hard segment ratio of the polyurethane elastomer and adding nanomaterials such as modified spiral carbon nanotubes, the problem of polyurethane materials being easily damaged under high-speed impact loading is solved, and its impact resistance and mechanical strength are significantly improved.

CN119552339APending Publication Date: 2025-03-04LINYI SIKERUI POLYURETHANE MATERIALS CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411875041.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-19
Publication Date
2025-03-04

AI Technical Summary

Technical Problem

Polyurethane elastomers are susceptible to damage under high-speed impact loading and have a temperature sensitive effect, affecting their application as impact protection material.

Method used

By adjusting the ratio of soft and hard segments of the inner polyurethane elastomer and adding nanomaterials such as modified spiral carbon nanotubes, ionic liquids and hydrogen-containing silicone oil, their mechanical properties and impact resistance are improved.

Benefits of technology

The impact resistance and mechanical strength of polyurethane materials are significantly improved, the material cost is reduced, and the risk of damage is reduced under high-speed impact loading.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005196657770000031
    Figure BDA0005196657770000031
  • Figure BDA0005196657770000041
    Figure BDA0005196657770000041
  • Figure BDA0005196657770000042
    Figure BDA0005196657770000042
Patent Text Reader

Abstract

The invention discloses an anti-collision and anti-impact polyurethane material and a preparation method thereof, and relates to the technical field of high polymer materials. When the anti-collision and anti-impact polyurethane material is prepared, firstly, 1-vinyl imidazole reacts with bromoethanol to prepare ionic liquid; modifying a helical carbon nanotube by using modified pyrene and modified silsesquioxane to prepare a modified helical carbon nanotube; the preparation method comprises the following steps: reacting isophorone diisocyanate with 3, 5-di-tert-butyl-4-hydroxyphenylpropionic acid to prepare hindered phenol terminated isocyanate; the preparation method comprises the following steps: reacting isophorone diisocyanate, hindered phenol terminated isocyanate, polycarbonate diol, 4, 4 '-dithio diphenylamine, 1, 2-octylene glycol, an ionic liquid, the modified helical carbon nanotube and hydrogen-containing silicone oil, and curing to obtain the anti-collision and anti-impact polyurethane material. The anti-collision and impact-resistant polyurethane material prepared by the invention has the advantages of high impact strength, high mechanical strength, aging resistance and self-repairing.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of polymer materials, in particular to an anti-collision and impact-resistant polyurethane material and a preparation method thereof. Background Art

[0002] As the impact loads generated by special circumstances such as explosion impact, car collision and high-risk competitive sports continue to affect safety, the demand for impact protection materials has shown an upward trend in various industries such as national defense, military industry, civilian field, sports industry, etc. Traditional protective materials include metal-based, ceramic-based and concrete-based composite materials. Although these materials have mature research technology and good impact resistance, they cannot meet the development requirements of the times that protective materials tend to be lightweight, high-performance and comfortable. In recent years, elastomer protective materials have made great achievements in the field of impact protection materials due to their advantages such as light weight, high energy absorption, softness and comfort. Polymer elastomer materials combine the characteristics of plastics and rubber. They are not only highly processable like plastics, but also have excellent mechanical properties similar to rubber. In addition, polymer elastomers will respond when subjected to static loads, showing viscoelastic or superelastic characteristics; they will harden when subjected to dynamic impact loads, showing high strain rate dependence. Among the many elastomers, polyurethane elastomers have become one of the most widely used elastomer materials in protective engineering after rubber due to their advantages such as high modulus, high elasticity and excellent flexibility. The protective mechanism of polyurethane elastomer is not like metal-based or concrete-based composite materials that rely on their own high hardness to resist impact and erosion. It mainly absorbs energy through its own plastic deformation and fracture damage. Based on this characteristic, polyurethane elastomer will not produce impact fragments in the explosion to cause secondary damage.

[0003] Polyurethane elastomers are widely used in the field of protective materials due to their light weight, excellent mechanical properties and strong comfort. However, polyurethane elastomers have a typical temperature-sensitive effect under high-speed impact loading. The softening caused by adiabatic compression and the tensile stress on the loading surface make them vulnerable to damage, which seriously affects their widespread application as impact protection materials. Adjusting the ratio of soft and hard segments inside polyurethane elastomers and adding different nanomaterials are two effective methods to enhance their mechanical properties. Among them, the method of enhancing polyurethane elastomers with nanomaterials has the advantages of simple process, strong operability and greatly reduced material costs while improving the mechanical properties of polyurethane elastomers. Summary of the invention

[0004] The purpose of the present invention is to provide an anti-collision and impact-resistant polyurethane material and a preparation method thereof, so as to solve the problems existing in the prior art.

[0005] In order to solve the above technical problems, the present invention provides the following technical solutions:

[0006] A collision-proof and impact-resistant polyurethane material, wherein the collision-proof and impact-resistant polyurethane material is obtained by curing isophorone diisocyanate, hindered phenol-terminated isocyanate, polycarbonate diol, 4,4'-dithiodiphenylamine, 1,2-octanediol, ionic liquid, modified helical carbon nanotubes, and hydrogen-containing silicone oil to obtain the collision-proof and impact-resistant polyurethane material;

[0007] The hindered phenol-terminated isocyanate is prepared by reacting isophorone diisocyanate with 3,5-di-tert-butyl-4-hydroxyphenylpropionic acid;

[0008] The ionic liquid is prepared by reacting 1-vinylimidazole with bromoethanol;

[0009] The modified helical carbon nanotube is prepared by modifying the helical carbon nanotube with modified pyrene and modified silsesquioxane.

[0010] As an optimization, the polycarbonate diol model is P997425, and the weight average molecular weight is 500.

[0011] As an optimization, the hydrogen-containing silicone oil model is JN-202, with a hydrogen content of 1.58%, purchased from Shandong Juneng Chemical Co., Ltd.

[0012] As an optimization, the modified pyrene is prepared by reacting 1-hydroxypyrene with isocyanatepropyltriethoxysilane.

[0013] As an optimization, the modified silsesquioxane is prepared by reacting octavinyl silsesquioxane with 3-mercaptopropyltriethoxysilane.

[0014] As an optimization, the spiral carbon nanotube has a diameter of 100-200 nm, a tube length of 1-10 μm, item number 100341, and is purchased from Jiangsu Xianfeng Nanomaterial Technology Co., Ltd.

[0015] A method for preparing an anti-collision and impact-resistant polyurethane material comprises the following preparation steps:

[0016] (1) By weight, 4 to 5 parts of 1-hydroxypyrene, 4.99 to 6.23 parts of isocyanatepropyltriethoxysilane, 50 to 60 parts of ethyl acetate, 0.01 to 0.02 parts of triethylamine, and 0.05 to 0.06 parts of dibutyltin dilaurate are mixed uniformly, refluxed at 78 to 80° C. and 300 to 400 r / min for 6 to 7 hours, and the solvent is removed by rotary evaporation to obtain modified pyrene;

[0017] (2) by weight, 6 to 7 parts of octavinyl silsesquioxane, 9.04 to 10.55 parts of 3-mercaptopropyltriethoxysilane, 50 to 60 parts of toluene, and 0.03 to 0.04 parts of azobisisobutyronitrile were mixed uniformly, and refluxed at 80 to 85° C. and 300 to 400 r / min for 3 to 4 hours, and the precipitate was removed by filtration, and the toluene was removed by rotary evaporation to obtain a modified silsesquioxane;

[0018] (3) By weight, 0.8-1 parts of helical carbon nanotubes, 0.6-0.8 parts of modified pyrene, and 40-50 parts of ethanol hydrolyzate were mixed uniformly, stirred at 600-800 r / min for 20-30 min at room temperature, 0.52-0.7 parts of modified silsesquioxane were added, stirred at 600-800 r / min for 30-40 min at room temperature, refluxed at 70-75° C. and 300-400 r / min for 6-8 h, the solvent was removed by rotary evaporation, and vacuum dried at 50-60° C. for 8-10 h to obtain modified helical carbon nanotubes;

[0019] (4) Mix 9-10 parts of 1-vinyl imidazole and 14.34-15.93 parts of bromoethanol by weight, reflux for reaction at 78-82° C. and 200-300 r / min for 12-14 h under a nitrogen atmosphere, cool naturally to room temperature, wash with ether 3-4 times, and vacuum dry at 50-60° C. for 6-8 h to obtain an ionic liquid;

[0020] (5) Under a nitrogen atmosphere, isophorone diisocyanate and 3,5-di-tert-butyl-4-hydroxyphenylpropionic acid are mixed uniformly, reacted at 80-85° C. and 150-200 r / min for 3-4 hours, and after sampling to confirm that the reaction is complete, the mixture is naturally cooled to room temperature to obtain hindered phenol-terminated isocyanate;

[0021] (6) According to the parts by mass, under a nitrogen atmosphere, 25-30 parts of isophorone diisocyanate, 20.54-24.65 parts of hindered phenol-terminated isocyanate, and 0.91-1.09 parts of dibutyltin dilaurate were mixed uniformly, stirred at 60-70°C and 150-250 r / min for 15-20 min, 33.74-43.18 parts of polycarbonate diol were added, and the mixture was reacted at 60-70°C and 200-300 r / min for 2.5-3 h, 6.26-7.5 parts of 4,4'-dithiodiphenylamine were added, and the mixture was reacted at 65-75°C and 200-300 r / min for 3-4 h, and 2.63-3. 68 parts of 1,2-octanediol are reacted at 70-80°C and 300-400 r / min for 3-4 hours, 9.85-13.24 parts of ionic liquid are added, and reflux reaction is carried out at 70-80°C and 350-450 r / min for 4-5 hours, 4.92-5.99 parts of modified helical carbon nanotubes, 9.8-11.98 parts of hydrogen-containing silicone oil, and 0.2-0.24 parts of chloroplatinic acid are added, and the mixture is stirred at 75-85°C and 500-600 r / min for 10-15 minutes, vacuumed for 1-2 minutes, poured into a mold, cured in a drying oven at 100°C for 16-20 hours, and cured at room temperature for 7 days to obtain an anti-collision and impact-resistant polyurethane material.

[0022] As an optimization, the reaction process of the modified pyrene in step (1) is as follows:

[0023]

[0024] As an optimization, the reaction process of the modified silsesquioxane in step (2) is as follows:

[0025]

[0026] As an optimization, the ethanol hydrolyzate in step (3) is prepared by uniformly mixing anhydrous ethanol and pure water in a volume ratio of 3:1.

[0027] As an optimization, the reaction process of the ionic liquid in step (4) is as follows:

[0028]

[0029] As an optimization, the reaction process of the hindered phenol-terminated isocyanate in step (5) is as follows:

[0030]

[0031] As an optimization, the isophorone diisocyanate and 3,5-di-tert-butyl-4-hydroxyphenylpropionic acid in step (5) are added in a molar ratio of 1:1.

[0032] As an optimization, the mold in step (6) is preheated to 100°C in advance.

[0033] Compared with the prior art, the beneficial effects achieved by the present invention are:

[0034] When preparing the anti-collision and impact-resistant polyurethane material, the present invention firstly reacts 1-hydroxypyrene with isocyanatepropyl triethoxysilane to obtain modified pyrene; reacts octavinyl silsesquioxane with 3-mercaptopropyl triethoxysilane to obtain modified silsesquioxane; uses the modified pyrene and the modified silsesquioxane to modify spiral carbon nanotubes to obtain modified spiral carbon nanotubes; reacts 1-vinyl imidazole with bromoethanol to obtain ionic liquid; reacts isophorone diisocyanate with 3,5-di-tert-butyl-4-hydroxyphenyl propionic acid to obtain hindered phenol-terminated isocyanate; reacts isophorone diisocyanate, polycarbonate diol, 4,4'-dithiodiphenylamine, 1,2-octanediol, ionic liquid, modified spiral carbon nanotubes, and hydrogen-containing silicone oil, and then solidifies the reacted carbon nanotubes to obtain the anti-collision and impact-resistant polyurethane material.

[0035] Firstly, 1-hydroxypyrene is reacted with isocyanatepropyltriethoxysilane to obtain modified pyrene, and the siloxane group is grafted onto the hydroxypyrene by the reaction of isocyanate group and hydroxyl group; then, octavinylsilsesquioxane is reacted with 3-mercaptopropyltriethoxysilane to obtain modified silsesquioxane, and the siloxane group is introduced into the silsesquioxane through the click reaction of mercapto group and olefin, thereby improving the substrate compatibility of the silsesquioxane and introducing the thioether group; in the presence of hindered phenol, the thioether group can synergistically enhance the anti-aging effect; the helical carbon nanotubes are modified with modified pyrene and modified silsesquioxane to obtain modified helical carbon nanotubes, and the modified pyrene is modified on the surface of the helical carbon nanotubes by π-π conjugation. This non-covalent bond modification form improves the dispersibility of the helical carbon nanotubes while avoiding the destruction of the stable hexagonal structure of the helical carbon nanotubes, thereby ensuring the improvement of mechanical strength, and at the same time The siloxane groups on the modified pyrene and the siloxane groups on the modified silsesquioxane are hydrolyzed to produce silanol groups with self-crosslinking ability. The modified silsesquioxane is grafted on the surface of the spiral carbon nanotube while improving the compatibility. The π-bridge modification formed by π-π conjugation can form a good stress transfer structure, which effectively improves the impact resistance. At the same time, the modified silsesquioxane has a cage-like hollow high-toughness structure. While the spiral carbon nanotube is used as a "nail column", the modified silsesquioxane is used as the "nail column" cavity. The combination of the two can effectively alleviate the problems of high specific surface energy and poor compatibility of the spiral carbon nanotube. In order to give full play to the role of the two, the two are connected under the π-bridge modification formed by the π-π conjugation of the modified pyrene to form a unique stress transfer structure, which effectively improves the impact resistance and retains the carbon-carbon double bond due to subsequent crosslinking.

[0036] Secondly, 1-vinylimidazole is reacted with bromoethanol to obtain an ionic liquid. The prepared ionic liquid has both reactive hydroxyl groups and carbon-carbon double bonds. Under the ionic bond modification of the ionic liquid, while improving the mechanical strength, the modified spiral carbon nanotubes can be connected to the polyurethane matrix through free radical reaction or hydrosilylation reaction, thereby further improving the compatibility between the two. Isophorone diisocyanate is reacted with 3,5-di-tert-butyl-4-hydroxyphenylpropionic acid to obtain hindered phenol-terminated isocyanate, and the hindered phenol structure is introduced into the polyurethane in the form of a prepolymer. The hindered phenol structure has good anti-aging properties, and the anti-aging effect can be further improved under the synergistic effect of the thioether structure, thereby effectively improving the service life of the polyurethane substrate in various environments.

[0037] Finally, isophorone diisocyanate, hindered phenol-terminated isocyanate, polycarbonate diol, 4,4'-dithiodiphenylamine, 1,2-octanediol, ionic liquid, modified helical carbon nanotubes, and hydrogen-containing silicone oil were reacted and cured to obtain an anti-collision and impact-resistant polyurethane material. 4,4'-dithiodiphenylamine introduced disulfide bonds into polyurethane. As a dynamic covalent bond, the disulfide bond has a self-repairing effect. After the introduction of the disulfide bond, the generation of microcracks can be effectively inhibited and the mechanical strength and impact resistance can be improved. At the same time, the amino groups at both ends and the isocyanate groups form a structure containing more hydrogen bonds, which improves the mechanical strength and the self-repairing effect of the disulfide bond. At the same time, hydrogen bonds, as secondary bonds, have lower fracture energy. Under the impact of external force, the impact energy can be absorbed by preferentially breaking hydrogen bonds, and the damage to the main structure of the polyurethane can be reduced. At the same time, after the impact disappears, the hydrogen bonds can be re-formed and gradually restore the original strength, which effectively improves the impact resistance. 1,2-Octanediol acts as a chain extender and has a long carbon chain side chain. This side chain can be inserted into other chain segment structures to enhance the effect of chain segment entanglement. The presence of the long carbon chain also improves the compatibility of the soft and hard segments of the polyurethane, increases the degree of hydrogen bonding, and helps to improve the compatibility between the modified spiral carbon nanotubes and the polyurethane matrix, giving full play to the effect of the modified spiral carbon nanotubes on improving impact resistance and mechanical strength. The ionic liquid is grafted onto the polyurethane main chain through hydroxyl groups, and its remaining carbon-carbon double bonds can produce cross-linking effects through free radical reactions or silane addition reactions to further enhance the mechanical strength and impact resistance. The hydrogenated silicone oil has silicon-hydrogen bonds that can react with carbon-carbon double bonds. Under the action of chloroplatinic acid, it can simultaneously undergo silane addition reactions with the carbon-carbon double bonds on the polyurethane main chain and the modified spiral carbon nanotubes to cross-link the two together. The silane segment of the hydrogenated silicone oil can also further improve the microphase separation degree of the polyurethane matrix, thereby improving the mechanical strength and impact resistance. DETAILED DESCRIPTION

[0038] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.

[0039] Embodiment 1:

[0040] A method for preparing an anti-collision and impact-resistant polyurethane material, the method for preparing an anti-collision and impact-resistant polyurethane material comprising the following preparation steps:

[0041] (1) By weight, 4 parts of 1-hydroxypyrene, 4.99 parts of isocyanatepropyltriethoxysilane, 50 parts of ethyl acetate, 0.01 parts of triethylamine, and 0.05 parts of dibutyltin dilaurate were mixed uniformly, refluxed at 78° C. and 300 r / min for 7 h, and the solvent was removed by rotary evaporation to obtain modified pyrene;

[0042] (2) 6 parts of octavinyl silsesquioxane, 9.04 parts of 3-mercaptopropyltriethoxysilane, 50 parts of toluene, and 0.03 parts of azobisisobutyronitrile were mixed uniformly by weight, and refluxed at 80° C. and 300 r / min for 4 h, the precipitate was removed by filtration, and the toluene was removed by rotary evaporation to obtain modified silsesquioxane;

[0043] (3) By weight, 0.8 parts of helical carbon nanotubes, 0.6 parts of modified pyrene, and 40 parts of ethanol hydrolyzate were mixed evenly, stirred at 600 r / min for 30 min at room temperature, 0.52 parts of modified silsesquioxane were added, stirred at 600 r / min for 40 min at room temperature, refluxed at 70°C and 300 r / min for 8 h, the solvent was removed by rotary evaporation, and vacuum dried at 50°C for 10 h to obtain modified helical carbon nanotubes;

[0044] (4) 9 parts of 1-vinyl imidazole and 14.34 parts of bromoethanol were mixed uniformly by weight, refluxed at 78°C and 200 r / min for 14 h under a nitrogen atmosphere, cooled naturally to room temperature, washed with ether three times, and vacuum dried at 50°C for 8 h to obtain an ionic liquid;

[0045] (5) Under a nitrogen atmosphere, isophorone diisocyanate and 3,5-di-tert-butyl-4-hydroxyphenylpropionic acid were mixed uniformly in a molar ratio of 1:1, reacted at 80° C. and 150 r / min for 4 h, and after sampling to confirm that the reaction was complete, the mixture was naturally cooled to room temperature to obtain a hindered phenol-terminated isocyanate;

[0046] (6) According to the parts by mass, under a nitrogen atmosphere, 25 parts of isophorone diisocyanate, 20.54 parts of hindered phenol-terminated isocyanate, and 0.91 parts of dibutyltin dilaurate were mixed uniformly, stirred at 60°C and 150 r / min for 20 min, 33.74 parts of polycarbonate diol were added, and the mixture was reacted at 60°C and 200 r / min for 3 h. 6.7 parts of 4,4'-dithiodiphenylamine were added, and the mixture was reacted at 65°C and 200 r / min for 4 h. 2.63 parts of 1,2- Octanediol was reacted at 70°C and 300 r / min for 4 hours, 9.85 parts of ionic liquid were added, and refluxed at 70°C and 350 r / min for 5 hours. 4.92 parts of modified helical carbon nanotubes, 9.8 parts of hydrogenated silicone oil and 0.2 parts of chloroplatinic acid were added, and stirred at 75°C and 500 r / min for 15 minutes. The mixture was vacuumed for 1 minute and poured into a mold preheated at 100°C. The mixture was cured in a drying oven at 100°C for 16 hours and cured at room temperature for 7 days to obtain an anti-collision and impact-resistant polyurethane material.

[0047] Embodiment 2:

[0048] A method for preparing an anti-collision and impact-resistant polyurethane material, the method for preparing an anti-collision and impact-resistant polyurethane material comprising the following preparation steps:

[0049] (1) By weight, 4.5 parts of 1-hydroxypyrene, 5.61 parts of isocyanatepropyltriethoxysilane, 55 parts of ethyl acetate, 0.015 parts of triethylamine, and 0.055 parts of dibutyltin dilaurate were mixed uniformly, refluxed at 79° C. and 350 r / min for 6.5 h, and the solvent was removed by rotary evaporation to obtain modified pyrene;

[0050] (2) 6.5 parts of octavinyl silsesquioxane, 9.79 parts of 3-mercaptopropyltriethoxysilane, 55 parts of toluene, and 0.035 parts of azobisisobutyronitrile were mixed uniformly by weight, and refluxed at 82° C. and 350 r / min for 3.5 h, the precipitate was removed by filtration, and the toluene was removed by rotary evaporation to obtain modified silsesquioxane;

[0051] (3) By weight, 0.9 parts of helical carbon nanotubes, 0.7 parts of modified pyrene, and 45 parts of ethanol hydrolyzate were mixed evenly, stirred at 700 r / min for 25 min at room temperature, 0.61 parts of modified silsesquioxane were added, stirred at 700 r / min for 35 min at room temperature, refluxed at 72° C. and 350 r / min for 7 h, the solvent was removed by rotary evaporation, and vacuum dried at 55° C. for 9 h to obtain modified helical carbon nanotubes;

[0052] (4) 9.5 parts of 1-vinyl imidazole and 15.14 parts of bromoethanol were mixed uniformly by weight, refluxed at 80°C and 250 r / min for 13 h under a nitrogen atmosphere, cooled naturally to room temperature, washed with ether 4 times, and vacuum dried at 55°C for 7 h to obtain an ionic liquid;

[0053] (5) Under a nitrogen atmosphere, isophorone diisocyanate and 3,5-di-tert-butyl-4-hydroxyphenylpropionic acid were mixed uniformly in a molar ratio of 1:1, reacted at 85° C. and 175 r / min for 3.5 h, and after sampling to confirm that the reaction was complete, the mixture was naturally cooled to room temperature to obtain a hindered phenol-terminated isocyanate;

[0054] (6) According to the parts by mass, under a nitrogen atmosphere, 28 parts of isophorone diisocyanate, 23 parts of hindered phenol-terminated isocyanate, and 1.02 parts of dibutyltin dilaurate were mixed uniformly, stirred at 65°C and 200 r / min for 18 min, 35.26 parts of polycarbonate diol were added, and the mixture was reacted at 65°C and 250 r / min for 3 h, 6.26 parts of 4,4'-dithiodiphenylamine were added, and the mixture was reacted at 70°C and 250 r / min for 3.5 h, 3.68 parts of 1,2-octanediol were added, The reaction was carried out at 75°C and 350 r / min for 3.5 hours, 13.24 parts of ionic liquid were added, and the reaction was refluxed at 75°C and 400 r / min for 4.5 hours. 5.47 parts of modified helical carbon nanotubes, 10.95 parts of hydrogenated silicone oil, and 0.22 parts of chloroplatinic acid were added, and the mixture was stirred at 80°C and 550 r / min for 12 minutes. The mixture was vacuumed for 2 minutes, and the mixture was poured into a mold preheated at 100°C. The mixture was cured in a drying oven at 100°C for 18 hours and cured at room temperature for 7 days to obtain an anti-collision and impact-resistant polyurethane material.

[0055] Embodiment 3:

[0056] A method for preparing an anti-collision and impact-resistant polyurethane material, the method for preparing an anti-collision and impact-resistant polyurethane material comprising the following preparation steps:

[0057] (1) 5 parts of 1-hydroxypyrene, 6.23 parts of isocyanatepropyltriethoxysilane, 60 parts of ethyl acetate, 0.02 parts of triethylamine, and 0.06 parts of dibutyltin dilaurate were mixed uniformly by mass, refluxed at 80° C. and 400 r / min for 6 h, and the solvent was removed by rotary evaporation to obtain modified pyrene;

[0058] (2) 7 parts of octavinyl silsesquioxane, 10.55 parts of 3-mercaptopropyltriethoxysilane, 60 parts of toluene, and 0.04 parts of azobisisobutyronitrile were mixed uniformly by weight, and refluxed at 85° C. and 400 r / min for 3 h, the precipitate was removed by filtration, and the toluene was removed by rotary evaporation to obtain modified silsesquioxane;

[0059] (3) According to the mass fraction, 1 part of helical carbon nanotubes, 0.8 parts of modified pyrene, and 50 parts of ethanol hydrolyzate were mixed evenly, stirred at 800 r / min for 20 min at room temperature, 0.7 parts of modified silsesquioxane were added, stirred at 800 r / min for 30 min at room temperature, refluxed at 75°C and 400 r / min for 6 h, the solvent was removed by rotary evaporation, and vacuum dried at 60°C for 8 h to obtain modified helical carbon nanotubes;

[0060] (4) 10 parts of 1-vinyl imidazole and 15.93 parts of bromoethanol were mixed uniformly by weight, refluxed at 82°C and 300 r / min for 12 h under a nitrogen atmosphere, naturally cooled to room temperature, washed with ether 4 times, and vacuum dried at 60°C for 6 h to obtain an ionic liquid;

[0061] (5) Under a nitrogen atmosphere, isophorone diisocyanate and 3,5-di-tert-butyl-4-hydroxyphenylpropionic acid were uniformly mixed in a molar ratio of 1:1, reacted at 85° C. and 200 r / min for 3 h, and after sampling to confirm that the reaction was complete, the mixture was naturally cooled to room temperature to obtain a hindered phenol-terminated isocyanate;

[0062] (6) By weight, 30 parts of isophorone diisocyanate, 24.65 parts of hindered phenol-terminated isocyanate, and 1.09 parts of dibutyltin dilaurate were mixed uniformly under a nitrogen atmosphere, stirred at 70°C and 250 r / min for 15 min, 43.18 parts of polycarbonate diol were added, and the mixture was reacted at 70°C and 300 r / min for 2.5 h, 7.5 parts of 4,4'-dithiodiphenylamine were added, and the mixture was reacted at 75°C and 300 r / min for 3 h, and 2.68 parts of 1,2-octanol were added. The diol was reacted at 80°C and 400 r / min for 3 hours, 11.83 parts of ionic liquid were added, and refluxed at 80°C and 450 r / min for 4 hours. 5.99 parts of modified helical carbon nanotubes, 11.98 parts of hydrogenated silicone oil and 0.24 parts of chloroplatinic acid were added, and stirred at 85°C and 600 r / min for 10 minutes. The mixture was vacuumed for 2 minutes and poured into a mold preheated at 100°C. The mixture was cured in a drying oven at 100°C for 20 hours and cured at room temperature for 7 days to obtain an anti-collision and impact-resistant polyurethane material.

[0063] Comparative Example 1:

[0064] The difference between the preparation method of the anti-collision and impact-resistant polyurethane material of Comparative Example 1 and Example 2 is that step (1) is not performed, and step (3) is modified as follows: 0.9 parts of spiral carbon nanotubes, 0.61 parts of modified silsesquioxane, and 45 parts of ethanol hydrolyzate are mixed uniformly by mass, stirred at 700 r / min for 35 min at room temperature, refluxed at 72° C. and 350 r / min for 7 h, the solvent is removed by rotary evaporation, and vacuum dried at 55° C. for 9 h to obtain modified spiral carbon nanotubes. The remaining steps are the same as those of Example 2.

[0065] Comparative Example 2:

[0066] The difference between the preparation method of the anti-collision and impact-resistant polyurethane material of Comparative Example 2 and Example 2 is that step (2) is not performed, and step (3) is modified as follows: 0.9 parts of spiral carbon nanotubes, 0.7 parts of modified pyrene, and 45 parts of ethanol hydrolyzate are mixed uniformly by mass, stirred at 700 r / min for 25 min at room temperature, refluxed at 72° C. and 350 r / min for 7 h, the solvent is removed by rotary evaporation, and vacuum dried at 55° C. for 9 h to obtain modified spiral carbon nanotubes. The remaining steps are the same as those of Example 2.

[0067] Comparative Example 3:

[0068] The preparation method of the anti-collision and impact-resistant polyurethane material of Comparative Example 3 is different from that of Example 2 in that steps (1), (2) and (3) are not performed, and step (6) is modified as follows: by weight, 28 parts of isophorone diisocyanate, 23 parts of hindered phenol-terminated isocyanate and 1.02 parts of dibutyltin dilaurate are mixed uniformly under a nitrogen atmosphere, stirred at 65° C. and 200 r / min for 18 min, 35.26 parts of polycarbonate diol are added, and the mixture is reacted at 65° C. and 250 r / min for 3 h, 6.26 parts of 4,4'-dithiodiphenylamine are added, and the mixture is stirred at 65° C. and 250 r / min for 3 h. 70°C, 250r / min for 3.5h, add 3.68 parts of 1,2-octanediol, react at 75°C, 350r / min for 3.5h, add 13.24 parts of ionic liquid, reflux at 75°C, 400r / min for 4.5h, add 10.95 parts of hydrogenated silicone oil and 0.22 parts of chloroplatinic acid, stir at 80°C, 550r / min for 12min, evacuate for 2min, pour into a mold preheated at 100°C, cure in a drying oven at 100°C for 18h, and cure at room temperature for 7 days to obtain an anti-collision and impact-resistant polyurethane material. The remaining steps are the same as those in Example 2.

[0069] Comparative Example 4:

[0070] The preparation method of the anti-collision and impact-resistant polyurethane material of Comparative Example 4 is different from that of Example 2 in that steps (1), (2) and (3) are not performed, and step (6) is modified as follows: by weight, 28 parts of isophorone diisocyanate, 23 parts of hindered phenol-terminated isocyanate and 1.02 parts of dibutyltin dilaurate are mixed uniformly under a nitrogen atmosphere, stirred at 65° C. and 200 r / min for 18 min, 35.26 parts of polycarbonate diol are added, and the mixture is reacted at 65° C. and 250 r / min for 3 h, 6.26 parts of 4,4'-dithiodiphenylamine are added, and the mixture is reacted at 70° C. and 250 r / min for 3 h. 0r / min for 3.5h, add 3.68 parts of 1,2-octanediol, react at 75°C, 350r / min for 3.5h, add 13.24 parts of ionic liquid, reflux at 75°C, 400r / min for 4.5h, add 5.47 parts of spiral carbon nanotubes, 10.95 parts of hydrogen-containing silicone oil, 0.22 parts of chloroplatinic acid, stir at 80°C, 550r / min for 12min, evacuate for 2min, pour into a mold preheated at 100°C, cure in a drying oven at 100°C for 18h, and cure at room temperature for 7 days to obtain an anti-collision and impact-resistant polyurethane material. The remaining steps are the same as in Example 2.

[0071] Comparative Example 5:

[0072] The preparation method of the anti-collision and impact-resistant polyurethane material of Comparative Example 5 is different from that of Example 2 in that step (4) is not performed, and step (6) is modified as follows: by weight, 28 parts of isophorone diisocyanate, 23 parts of hindered phenol-terminated isocyanate, and 1.02 parts of dibutyltin dilaurate are mixed uniformly under a nitrogen atmosphere, stirred at 65° C. and 200 r / min for 18 min, 50.38 parts of polycarbonate diol are added, reacted at 65° C. and 250 r / min for 3 h, and 6.26 parts of 4,4'-diisocyanate are added. Thiodiphenylamine was reacted at 70°C and 250 r / min for 3.5 hours, 3.68 parts of 1,2-octanediol were added, and the reaction was carried out at 75°C and 350 r / min for 3.5 hours. 5.57 parts of modified helical carbon nanotubes, 11.13 parts of hydrogenated silicone oil, and 0.22 parts of chloroplatinic acid were added, and the mixture was stirred at 80°C and 550 r / min for 12 minutes, and vacuumed for 2 minutes, and poured into a mold preheated at 100°C, and cured in a drying oven at 100°C for 18 hours, and cured at room temperature for 7 days to obtain an anti-collision and impact-resistant polyurethane material. The remaining steps are the same as those in Example 2.

[0073] Comparative Example 6:

[0074] The preparation method of the anti-collision and impact-resistant polyurethane material of Comparative Example 6 is different from that of Example 2 in that step (5) is not performed, and step (6) is modified as follows: by weight, 28 parts of isophorone diisocyanate and 0.56 parts of dibutyltin dilaurate are mixed uniformly under a nitrogen atmosphere, stirred at 65°C and 200 r / min for 18 min, 29.38 parts of polycarbonate diol are added, and the mixture is reacted at 65°C and 250 r / min for 3 h, 5.21 parts of 4,4'-dithiodiphenylamine are added, and the mixture is reacted at 70°C and 250 r / min for 3.5 h. h, add 3.07 parts of 1,2-octanediol, react at 75°C, 350r / min for 3.5h, add 11.04 parts of ionic liquid, reflux at 75°C, 400r / min for 4.5h, add 3.84 parts of modified helical carbon nanotubes, 7.67 parts of hydrogenated silicone oil, 0.16 parts of chloroplatinic acid, stir at 80°C, 550r / min for 12min, evacuate for 2min, pour into a mold preheated at 100°C, cure in a drying oven at 100°C for 18h, and cure at room temperature for 7 days to obtain an anti-collision and impact-resistant polyurethane material. The remaining steps are the same as those in Example 2.

[0075] Comparative Example 7:

[0076] The difference between the preparation method of the anti-collision and impact-resistant polyurethane material of Comparative Example 7 and that of Example 2 lies in the difference in step (6). Step (6) is modified as follows: by weight, 28 parts of isophorone diisocyanate, 23 parts of hindered phenol-terminated isocyanate, and 1.02 parts of dibutyltin dilaurate are mixed uniformly under a nitrogen atmosphere, stirred at 65° C. and 200 r / min for 18 min, 40.3 parts of polycarbonate diol are added, and the mixture is reacted at 65° C. and 250 r / min for 3 h, and 10 parts of 4,4'-dithiodiol are added. Diphenylamine was reacted at 70°C and 250 r / min for 3.5 hours, 13.24 parts of ionic liquid were added, refluxed at 75°C and 400 r / min for 4.5 hours, 5.72 parts of modified helical carbon nanotubes, 11.46 parts of hydrogenated silicone oil, and 0.23 parts of chloroplatinic acid were added, stirred at 80°C and 550 r / min for 12 minutes, vacuumed for 2 minutes, poured into a mold preheated at 100°C, cured in a drying oven at 100°C for 18 hours, and cured at room temperature for 7 days to obtain an anti-collision and impact-resistant polyurethane material. The remaining steps were the same as those in Example 2.

[0077] Comparative Example 8:

[0078] The difference between the preparation method of the anti-collision and impact-resistant polyurethane material of Comparative Example 8 and that of Example 2 lies in the difference in step (6). Step (6) is modified as follows: by weight, 28 parts of isophorone diisocyanate, 23 parts of hindered phenol-terminated isocyanate, and 1.02 parts of dibutyltin dilaurate are mixed uniformly under a nitrogen atmosphere, stirred at 65° C. and 200 r / min for 18 min, 40.3 parts of polycarbonate diol are added, reacted at 65° C. and 250 r / min for 3 h, and 5.89 parts of 1,2-octanol are added. The diol was reacted at 75°C and 350r / min for 3.5h, 13.24 parts of ionic liquid were added, refluxed at 75°C and 400r / min for 4.5h, 5.52 parts of modified helical carbon nanotubes, 11.04 parts of hydrogenated silicone oil, and 0.22 parts of chloroplatinic acid were added, stirred at 80°C and 550r / min for 12min, vacuumed for 2min, poured into a mold preheated at 100°C, cured in a drying oven at 100°C for 18h, and cured at room temperature for 7 days to obtain an anti-collision and impact-resistant polyurethane material. The remaining steps are the same as those in Example 2.

[0079] Comparative Example 9:

[0080] The preparation method of the anti-collision and impact-resistant polyurethane material of Comparative Example 9 is different from that of Example 2 in that step (6) is different. Step (6) is modified as follows: by weight, 28 parts of isophorone diisocyanate, 23 parts of hindered phenol-terminated isocyanate, and 1.02 parts of dibutyltin dilaurate are mixed uniformly under a nitrogen atmosphere, stirred at 65° C. and 200 r / min for 18 min, 35.26 parts of polycarbonate diol are added, and the mixture is reacted at 65° C. and 250 r / min for 3 h, 6.26 parts of 4,4'-dithiodiphenylamine are added, and the mixture is reacted at 70° C. and 250 r / min for 3 h. 0r / min for 3.5h, add 3.68 parts of 1,2-octanediol, react at 75°C, 350r / min for 3.5h, add 13.24 parts of ionic liquid, reflux at 75°C, 400r / min for 4.5h, add 5.47 parts of modified helical carbon nanotubes and 0.2 parts of azobisisobutyronitrile, stir at 80°C, 550r / min for 12min, evacuate for 2min, pour into a mold preheated at 100°C, cure in a drying oven at 100°C for 18h, and cure at room temperature for 7 days to obtain an anti-collision and impact-resistant polyurethane material. The remaining steps are the same as in Example 2.

[0081] Comparative Example 10:

[0082] The preparation method of the anti-collision and impact-resistant polyurethane material of Comparative Example 10 is different from that of Example 2 in step (6). Step (6) is modified as follows: by mass, 28 parts of isophorone diisocyanate, 23 parts of hindered phenol-terminated isocyanate, and 1.02 parts of dibutyltin dilaurate are mixed uniformly under a nitrogen atmosphere, stirred at 65° C. and 200 r / min for 18 min, 35.26 parts of polycarbonate diol are added, and the reaction is carried out at 65° C. and 250 r / min for 3 h, 6.26 parts of 4,4'-dithiodiphenylamine are added, and the mixture is stirred at 200 r / min for 18 min. 70°C, 250r / min for 3.5h, add 3.68 parts of 1,2-octanediol, react at 75°C, 350r / min for 3.5h, add 13.24 parts of ionic liquid, reflux at 75°C, 400r / min for 4.5h, add 5.47 parts of modified helical carbon nanotubes, stir at 80°C, 550r / min for 12min, evacuate for 2min, pour into a mold preheated at 100°C, cure in a drying oven at 100°C for 18h, and cure at room temperature for 7 days to obtain an anti-collision and impact-resistant polyurethane material. The remaining steps are the same as in Example 2.

[0083] Test Example 1:

[0084] Mechanical properties test: The tensile strength and elongation at break of the prepared anti-collision and impact-resistant polyurethane material were tested to evaluate its mechanical strength. The tensile strength and elongation at break of the prepared anti-collision and impact-resistant polyurethane material were tested according to GB / T 1040.2-2022. The sample shape was 1A type sample, the tensile rate was 5 mm / min, and each group of samples was tested 5 times, and the average value was recorded.

[0085] The results are shown in Table 1.

[0086] Table 1

[0087] Tensile Strength Elongation at break Example 1 51.35MPa 562.27% Example 2 53.47MPa 580.16% Example 3 50.89MPa 575.95% Comparative Example 1 37.26MPa 521.24% Comparative Example 2 40.32MPa 532.64% Comparative Example 3 28.14MPa 483.14% Comparative Example 4 35.25MPa 510.59% Comparative Example 5 42.68MPa 431.48% Comparative Example 6 48.96MPa 470.15% Comparative Example 7 39.43MPa 381.32% Comparative Example 8 42.39MPa 438.73% Comparative Example 9 43.75MPa 421.91% Comparative Example 10 42.53MPa 370.96%

[0088] From the comparison of the experimental data of Examples 1 to 3 and Comparative Examples 1 to 10 in Table 1, it can be found that the anti-collision and impact-resistant polyurethane material prepared by the present invention has good tensile strength and elongation at break.

[0089] Comparison of the data in the table shows that the modification of helical carbon nanotubes and the addition of modified helical carbon nanotubes can effectively improve the tensile strength and elongation at break. The hydrogenated silicone oil undergoes a silylation reaction with the ionic liquid and the carbon-carbon double bonds on the modified helical carbon nanotubes to crosslink the nanofiller with the polyurethane matrix. At the same time, the silane segment of the hydrogenated silicone oil promotes microphase separation, which also improves the tensile strength and elongation at break. 4,4'-dithiodiphenylamine and 1,2-octanediol act as chain extenders, providing more hydrogen bond formation. The long carbon chain of 1,2-octanediol promotes the compatibility of the soft and hard segments, increases the degree of hydrogen bonding, and effectively improves the tensile strength and elongation at break.

[0090] Test Example 2:

[0091] Impact resistance test: Test the compressive yield strength, impact yield strength and energy absorption of the prepared anti-collision and impact-resistant polyurethane material to evaluate its impact resistance. The specific test method is as follows:

[0092] Compressive yield strength: The anti-collision and impact-resistant polyurethane material was subjected to static compression test using an electronic universal testing machine. The experimental process was based on GB / T 1041-2008. The maximum range of the universal testing machine was 100kN, and the compression specimen was a Φ20×4mm cylinder. To ensure the accuracy of the experimental results, the specimen was preloaded at a preload rate of 5mm / min, in order to allow the compression device to accurately contact the specimen and reduce the error of manual testing. After the preload of the test was completed, a static compression test was performed on the specimen at a compression rate of 1.2mm / min, and the specimen was compressed to a strain of 12.5%, that is, compressed to 3.5mm. Each group of samples was tested 5 times, and the average value was recorded.

[0093] Impact yield strength and energy absorption: With reference to GB / T 34108-2017, a split Hopkinson pressure bar system was used to carry out an impact test on the prepared anti-collision and impact-resistant polyurethane material. The specific size of the specimen was Φ10×2mm. The impact force of a single test was controlled to be 0.2MPa. The impact yield strength and energy absorption were calculated by obtaining the stress-strain curve. Each group of specimens was repeated 5 times, and the average value was recorded.

[0094] The results are shown in Table 2.

[0095] Table 2

[0096] Compressive yield strength Impact yield strength Energy Absorption Example 1 13.24MPa 32.25MPa <![CDATA[105.34J / cm 3 ]]> Example 2 13.68MPa 33.17MPa <![CDATA[107.26J / cm 3 ]]> Example 3 12.98MPa 32.59MPa <![CDATA[106.75J / cm 3 ]]> Comparative Example 1 8.14MPa 22.34MPa <![CDATA[72.31J / cm 3 ]]> Comparative Example 2 7.25MPa 19.67MPa <![CDATA[65.67J / cm 3 ]]> Comparative Example 3 5.37MPa 15.24MPa <![CDATA[43.19J / cm 3 ]]> Comparative Example 4 6.95MPa 18.57MPa <![CDATA[59.66J / cm 3 ]]> Comparative Example 5 9.34MPa 25.39MPa <![CDATA[81.32J / cm 3 ]]> Comparative Example 6 12.34MPa 31.27MPa <![CDATA[98.39J / cm 3 ]]> Comparative Example 7 9.25MPa 26.19MPa <![CDATA[79.24J / cm 3 ]]> Comparative Example 8 9.87MPa 28.63MPa <![CDATA[76.39J / cm 3 ]]> Comparative Example 9 11.15MPa 30.86MPa <![CDATA[93.34J / cm 3 ]]> Comparative Example 10 7.34MPa 21.67MPa <![CDATA[67.69J / cm 3 ]]>

[0097] From the comparison of the experimental data of Examples 1 to 3 and Comparative Examples 1 to 10 in Table 2, it can be found that the anti-collision and impact-resistant polyurethane material prepared by the present invention has good impact resistance.

[0098] By comparing the data in the table, it is shown that the modification of spiral carbon nanotubes and the addition of modified spiral carbon nanotubes effectively improve the impact resistance. The π bridge formed by the π-π conjugation of modified pyrene and the "nail column" cavity structure formed by modified silsesquioxane have good stress transfer effect and energy absorption performance. The special morphology of spiral carbon nanotubes also provides better mechanical interlocking performance, thereby improving the impact resistance of anti-collision and impact-resistant polyurethane materials; the ionization modification of ionic liquids and the intermediate bridging effect promote the impact resistance of modified spiral carbon nanotubes. Hydrogen-containing silicone oil is used as a cross-linking agent to connect the polyurethane matrix with the modified spiral carbon nanotubes, effectively improving the impact resistance; 4,4'-dithiodiphenylamine and 1,2-octanediol are used as chain extenders to provide more hydrogen bond formation. The long carbon chain of 1,2-octanediol promotes the compatibility of soft and hard segments and improves the degree of hydrogen bonding. More hydrogen bonds can be broken preferentially when external force impacts to absorb external impact energy, thereby protecting the polyurethane matrix.

[0099] Test Example 3:

[0100] Anti-aging and self-repairing performance test: The tensile strength loss rate of the prepared anti-collision and impact-resistant polyurethane material after UV irradiation aging is tested to evaluate its anti-aging performance, and the tensile strength retention rate of the prepared anti-collision and impact-resistant polyurethane material after self-repair is tested to evaluate its self-repairing performance. The specific test methods are as follows:

[0101] Anti-aging test: The prepared anti-collision and impact-resistant polyurethane material is made into specimens according to the tensile strength test method, and its tensile strength is tested in advance. Then, referring to the standard of GB / T 16422.3-2022, the specimens are artificially accelerated aged for 10 days using a FR-1205-QUV ultraviolet aging tester, and their tensile strength is tested again to calculate the tensile strength loss rate; each group of specimens is tested 5 times, and the average value is recorded.

[0102] Self-repair test: The prepared anti-collision and impact-resistant polyurethane material is made into a tensile strength specimen, and a scratch is cut on the surface of the middle section of the specimen using a scalpel. The scratch length is the width of the specimen at that part, and the depth is about 1 mm. The scratched specimen is repaired at 70°C for 24 hours, and the repaired specimen is tested for tensile strength according to the tensile strength test method and compared with the tensile strength measured in Test Example 1 to calculate the tensile strength retention rate. Each group of specimens is tested 5 times, and the average value is recorded.

[0103] The results are shown in Table 3.

[0104] Table 3

[0105]

[0106]

[0107] From the comparison of the experimental data of Examples 1 to 3 and Comparative Examples 1 to 10 in Table 3, it can be found that the anti-collision and impact-resistant polyurethane material prepared by the present invention has good anti-aging and self-repairing properties.

[0108] Comparison of the data in the table shows that the sulfide bonds on the modified silsesquioxane can cooperate with the hindered phenol structure to improve the anti-aging effect; 4,4'-disulfide diphenylamine introduces disulfide bonds while also providing the formation of more hydrogen bonds. The long carbon chain of 1,2-octanediol promotes the compatibility of the soft and hard segments, increases the degree of hydrogen bonding, and promotes the formation of more hydrogen bonds. Under appropriate external stimuli, these dynamic bonds reform and improve strength. Its self-healing effect enables it to cope with more complex usage environments and extend its service life.

[0109] The specific implementation methods described above further illustrate the objectives, technical solutions and beneficial effects of the present invention in detail. It should be understood that the above description is only a specific implementation method of the present invention and is not intended to limit the scope of protection of the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the scope of protection of the present invention.

Claims

1. A collision-proof and impact-resistant polyurethane material, characterized in that: The anti-collision and impact-resistant polyurethane material is prepared by curing isophorone diisocyanate, hindered phenol-terminated isocyanate, polycarbonate diol, 4,4'-dithiodiphenylamine, 1,2-octanediol, ionic liquid, modified helical carbon nanotubes, and hydrogen-containing silicone oil to obtain the anti-collision and impact-resistant polyurethane material. The hindered phenol-terminated isocyanate is prepared by reacting isophorone diisocyanate with 3,5-di-tert-butyl-4-hydroxyphenylpropionic acid; The ionic liquid is prepared by reacting 1-vinylimidazole with bromoethanol; The modified helical carbon nanotube is prepared by modifying the helical carbon nanotube with modified pyrene and modified silsesquioxane.

2. The anti-collision and impact-resistant polyurethane material according to claim 1, characterized in that: The polycarbonate diol model is P997425, and the weight average molecular weight is 500.

3. The anti-collision and impact-resistant polyurethane material according to claim 1, characterized in that: The model of the hydrogen-containing silicone oil is JN-202, and the hydrogen content is 1.58%.

4. The anti-collision and impact-resistant polyurethane material according to claim 1, characterized in that: The modified pyrene is prepared by reacting 1-hydroxypyrene with isocyanatepropyltriethoxysilane.

5. The anti-collision and impact-resistant polyurethane material according to claim 1, characterized in that: The modified silsesquioxane is prepared by reacting octavinyl silsesquioxane with 3-mercaptopropyltriethoxysilane.

6. A method for preparing an anti-collision and impact-resistant polyurethane material, characterized in that: The method comprises the following preparation steps: (1) By weight, 4 to 5 parts of 1-hydroxypyrene, 4.99 to 6.23 parts of isocyanatepropyltriethoxysilane, 50 to 60 parts of ethyl acetate, 0.01 to 0.02 parts of triethylamine, and 0.05 to 0.06 parts of dibutyltin dilaurate are mixed uniformly, refluxed at 78 to 80° C. and 300 to 400 r / min for 6 to 7 hours, and the solvent is removed by rotary evaporation to obtain modified pyrene; (2) by weight, 6 to 7 parts of octavinyl silsesquioxane, 9.04 to 10.55 parts of 3-mercaptopropyltriethoxysilane, 50 to 60 parts of toluene, and 0.03 to 0.04 parts of azobisisobutyronitrile were mixed uniformly, and refluxed at 80 to 85° C. and 300 to 400 r / min for 3 to 4 hours, and the precipitate was removed by filtration, and the toluene was removed by rotary evaporation to obtain a modified silsesquioxane; (3) By weight, 0.8-1 parts of helical carbon nanotubes, 0.6-0.8 parts of modified pyrene, and 40-50 parts of ethanol hydrolyzate were mixed uniformly, stirred at 600-800 r / min for 20-30 min at room temperature, 0.52-0.7 parts of modified silsesquioxane were added, stirred at 600-800 r / min for 30-40 min at room temperature, refluxed at 70-75° C. and 300-400 r / min for 6-8 h, the solvent was removed by rotary evaporation, and vacuum dried at 50-60° C. for 8-10 h to obtain modified helical carbon nanotubes; (4) Mix 9-10 parts of 1-vinyl imidazole and 14.34-15.93 parts of bromoethanol by weight, reflux for reaction at 78-82° C. and 200-300 r / min for 12-14 h under a nitrogen atmosphere, cool naturally to room temperature, wash with ether 3-4 times, and vacuum dry at 50-60° C. for 6-8 h to obtain an ionic liquid; (5) Under a nitrogen atmosphere, isophorone diisocyanate and 3,5-di-tert-butyl-4-hydroxyphenylpropionic acid are mixed uniformly, reacted at 80-85° C. and 150-200 r / min for 3-4 hours, and after sampling to confirm that the reaction is complete, the mixture is naturally cooled to room temperature to obtain hindered phenol-terminated isocyanate; (6) According to the parts by mass, under a nitrogen atmosphere, 25-30 parts of isophorone diisocyanate, 20.54-24.65 parts of hindered phenol-terminated isocyanate, and 0.91-1.09 parts of dibutyltin dilaurate were mixed uniformly, stirred at 60-70°C and 150-250 r / min for 15-20 min, 33.74-43.18 parts of polycarbonate diol were added, and the mixture was reacted at 60-70°C and 200-300 r / min for 2.5-3 h, 6.26-7.5 parts of 4,4'-dithiodiphenylamine were added, and the mixture was reacted at 65-75°C and 200-300 r / min for 3-4 h, and 2.63-3. 68 parts of 1,2-octanediol are reacted at 70-80°C and 300-400 r / min for 3-4 hours, 9.85-13.24 parts of ionic liquid are added, and reflux reaction is carried out at 70-80°C and 350-450 r / min for 4-5 hours, 4.92-5.99 parts of modified helical carbon nanotubes, 9.8-11.98 parts of hydrogen-containing silicone oil, and 0.2-0.24 parts of chloroplatinic acid are added, and the mixture is stirred at 75-85°C and 500-600 r / min for 10-15 minutes, vacuumed for 1-2 minutes, poured into a mold, cured in a drying oven at 100°C for 16-20 hours, and cured at room temperature for 7 days to obtain an anti-collision and impact-resistant polyurethane material.

7. The method for preparing the anti-collision and impact-resistant polyurethane material according to claim 6, characterized in that: The ethanol hydrolyzate in step (3) is prepared by uniformly mixing anhydrous ethanol and pure water in a volume ratio of 3:

1.

8. The method for preparing a collision-proof and impact-resistant polyurethane material according to claim 6, characterized in that: In step (5), isophorone diisocyanate and 3,5-di-tert-butyl-4-hydroxyphenylpropionic acid are added in a molar ratio of 1:

1.

9. The method for preparing a collision-proof and impact-resistant polyurethane material according to claim 6, characterized in that: In step (6), the mold is preheated to 100° C. in advance.